Effect of Glycoconjugation on Cytotoxicity and Selectivity of 8-Aminoquinoline Derivatives Compared to 8-Hydroxyquinoline - Gabriela Pastuch-Gawołek; Julia Szreder (Molecules)
Numerous emerging chemotherapeutic agents incorporate N-heterocyclic fragments in their structures, with the quinoline skeleton being particularly significant. Our recent works have focused on glycoconjugates of 8-hydroxyquinoline (8-HQ), which demonstrated enhanced bioavailability and solubility compared to their parent compounds, although they fell short in selectivity. In this study, our objective was to improve the selectivity of glycoconjugates by replacing the oxygen atom with nitrogen by substituting the 8-HQ moiety with 8-aminoquinoline (8-AQ). The 8-AQ derivatives were functionalized through the amino group and linked to sugar derivatives (D-glucose or D-galactose) that were modified with an azide, alkylazide, or propargyl group at the anomeric position by copper(I)-catalyzed 1,3-dipolar azido-alkyne cycloaddition (CuAAC). The resulting glycoconjugates, as well as their potential metabolites, were evaluated for their ability to inhibit the proliferation of cancer cell lines (including HCT 116 and MCF-7) and a healthy cell line (NHDF-Neo). Two of the synthesized glycoconjugates (17 and 18) demonstrated higher cytotoxicity than their oxygen-containing counterparts and showed improved selectivity for cancer cells, thus enhancing their anticancer potential. Furthermore, it was found that glycoconjugates exhibited greater cytotoxicity in comparison to their potential metabolites.